Palatalization in Ukrainian, Polish and Russian. A pilot 3D Ultrasound Study - Małgorzata E. Ćavar; Neha Nagaraj; Isabelle Amacker (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The paper reports findings of a pilot 3D/4D ultrasound study on the articulation of palatalized coronal obstruents in Ukrainian, Polish and Russian. The study quantitatively evaluates the degree of palatalization looking at the relative dorsum frontings/dorsum raising/ advancement of the tongue root as variables. Apart from the fronting and raising of the tongue dorsum, palatalized consonants show a systematic effect of the advancement of the tongue root. The preliminary results indicate that the effect of the position of the dorsum is bigger in phonemic palatalization than in allophonic palatalization, while the effect size of the tongue root remains similar across palatalization types.